Preparation method of perovskite active layer, perovskite battery and perovskite material

By adding self-assembled small molecules TIPSp to the perovskite precursor solution, an ordered ultrathin hole transport layer is formed, which solves the stability problem of hole transport layer materials in existing perovskite solar cells and improves charge transport capability and device performance.

CN119546151APending Publication Date: 2025-02-28旗滨新能源发展(深圳)有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986196.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In existing perovskite solar cells, commonly used hole transport layer materials such as Spiro-OMe and PTAA have stability issues, while inorganic NiOx materials react with perovskite, leading to interfacial decomposition. There is an urgent need to develop new self-assembly materials to improve device performance.

Method used

Adding the self-assembled small molecule 6,13-bis(triisopropylsilylethynyl)pentabenzene (TIPSp) to the perovskite precursor solution allows for the formation of an ordered ultrathin hole transport layer at the perovskite active layer interface through its steric hindrance and conjugated planar structure, thus avoiding the need for additional hole transport layer preparation.

Benefits of technology

It improves the interfacial contact of perovskite solar cells, reduces energy loss during hole transport, provides superior charge transport and charge extraction capabilities, and optimizes the fabrication process of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546151A_ABST
    Figure CN119546151A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite active layer, a perovskite battery and a perovskite material, and belongs to the technical field of perovskite batteries. According to the invention, the surface of a substrate is coated with a perovskite precursor solution to form a perovskite active layer; the perovskite precursor solution contains self-assembled small molecules, and the self-assembled small molecules comprise the following structural formula: # imgabs0 #. The self-assembled small molecules are applied to preparation of a perovskite active layer of a perovskite cell, an ordered and ultrathin hole transport layer can be formed on a buried interface of the perovskite active layer, the interface of the perovskite active layer is passivated, and the perovskite active layer is formed in the hole transport layer. And the interface contact of the perovskite active layer is improved, so that the energy loss in the hole transport process can be reduced, excellent charge transport and charge extraction capabilities are provided, and the perovskite cell has better device performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite battery technology, and in particular to a method for preparing a perovskite active layer, a perovskite battery, and perovskite materials. Background Technology

[0002] Perovskite materials have attracted increasing interest worldwide due to their excellent photoelectric properties, including high light absorption coefficient, tunable bandgap, high carrier mobility, bipolar carrier transport, low exciton binding energy, solution processability, and low cost. In the past decade, solar cells using perovskite as the light-absorbing layer have developed rapidly, with single-cell efficiencies exceeding 26%. However, current high-efficiency perovskite devices suffer from stability degradation due to the indispensable Spiro-OMe hole transport layer. In contrast, inverted devices offer a simpler structure and a wider selection of HTL materials. Organic hole-carrying materials include poly(3,4-ethylenedioxythiophene) (styrene sulfonate) and PTAA, although these are susceptible to photo- and heat-induced degradation. Furthermore, commonly used inorganic NiOx hole transport materials react with perovskite, causing interfacial decomposition. Therefore, there is an urgent need to develop a new self-assembly material that can effectively utilize the hole transport layer for perovskite solar cells, thereby improving the performance of perovskite devices. Summary of the Invention

[0003] Based on the background technology, the main objective of this invention is to provide a method for preparing a perovskite active layer, as well as a perovskite battery and perovskite materials.

[0004] To achieve the above objectives, the present invention provides a method for preparing a perovskite active layer, comprising the following steps:

[0005] The perovskite precursor solution is coated onto the surface of the substrate to form the perovskite active layer;

[0006] The perovskite precursor solution contains self-assembled small molecules;

[0007] The self-assembled small molecule includes the following structural formula:

[0008]

[0009] In some embodiments of the present invention, the method for preparing the self-assembled small molecule includes the following steps:

[0010] A mixture was obtained by dissolving n-butyllithium and triisopropylsilylacetylene in tetrahydrofuran, and a solution of compound A was obtained by dissolving compound A in tetrahydrofuran.

[0011] The mixture and the solution of compound A are mixed and heated to obtain a reactant. The reactant is then extracted and the solvent is removed to obtain a crude solid.

[0012] The crude solid was dissolved in an organic solvent, and acetic acid and tin chloride dihydrate solution were added. The mixture was stirred, reacted, and filtered to obtain a solid product.

[0013] The solid product was dissolved in an organic solvent and then washed, dried, and purified to obtain the self-assembled small molecule.

[0014] Compound A is pentabenzene-6,13-quinone, and has the following structural formula:

[0015]

[0016] In some embodiments of the present invention, the molar ratio of the n-butyllithium droplet, triisopropylsilylacetylene, and compound A is (30.5–50.5):(30.2–50.2):(6.2–26.2).

[0017] In some embodiments of the present invention, the mixture is stored at 0°C for 40 min to 60 min before being mixed with the compound A solution;

[0018] And / or, the temperature of compound A and the mixture before mixing is 0°C;

[0019] And / or, the temperature of the heating reaction is 25°C to 30°C;

[0020] And / or, the heating reaction time is 12h to 15h;

[0021] And / or, the mixture and the solution of compound A are mixed, heated and quenched to obtain a reactant, and the quenching reaction is completed with hydrochloric acid;

[0022] And / or, the extraction includes an extractant, the extractant including CHCl3;

[0023] And / or, the solvent is removed by rotary evaporation and / or filtration to obtain the crude solid.

[0024] In some embodiments of the present invention, the mass concentration of the acetic acid is 50%;

[0025] And / or, each 50 ml of acetic acid with a mass concentration of 50% contains 9.2 g to 12 g of tin chloride dihydrate;

[0026] And / or, the temperature of the stirring reaction is 25°C to 30°C;

[0027] And / or, the stirring reaction time is 20h to 24h.

[0028] In some embodiments of the present invention, the washing includes a detergent, the detergent comprising saturated sodium bicarbonate;

[0029] And / or, the drying includes a desiccant, the desiccant including anhydrous magnesium sulfate;

[0030] And / or, the purification includes an eluent comprising n-hexane and dichloromethane.

[0031] In some embodiments of the present invention, the amount of self-assembled small molecules added to the perovskite precursor solution is (0.3-10) mg / ml.

[0032] The present invention also provides a perovskite battery, wherein the perovskite battery comprises a perovskite active layer prepared by the method described above for preparing the perovskite active layer.

[0033] In some embodiments of the present invention, the perovskite solar cell further includes a transparent conductive oxide layer, wherein the perovskite active layer is disposed on the surface of the transparent conductive oxide layer.

[0034] In some embodiments of the present invention, the perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, a perovskite active layer, an electron transport layer, and a back electrode layer.

[0035] This invention also provides a perovskite material for use in perovskite batteries, wherein the perovskite material comprises self-assembled small molecules, and the self-assembled small molecules comprise the following structural formulas:

[0036]

[0037] The beneficial effects that this invention can achieve are:

[0038] In preparing the perovskite active layer for a perovskite solar cell, this invention adds a self-assembled small molecule, 6,13-bis(triisopropylsilylethynyl)pentabenzene (TIPSp), to the perovskite precursor solution. This allows for the preparation of a perovskite solar cell without pre-deposition of a hole layer. The steric hindrance caused by the thorny triisopropylsilyl groups in TIPSp and the large conjugated plane provided by the five benzene rings allow the molecule to be orderly extruded from the precursor solution to the grain boundaries and the bottom surface of the film. Simultaneously, the benzene rings are linked to the triisopropylsilyl groups through the ethynyl groups, thus... The molecule has a balanced charge distribution, which induces it to have tight stacking and favorable orientation. This allows it to form an ordered, ultrathin hole transport layer at the buried interface of the perovskite active layer, passivating the interface of the perovskite active layer and improving the interfacial contact. This not only reduces energy loss during hole transport and provides superior charge transport and extraction capabilities, resulting in better device performance for perovskite solar cells, but also eliminates the need for additional hole transport layer fabrication, thus optimizing the fabrication process of perovskite solar cells. Attached Figure Description

[0039] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0040] Figure 1 This is a schematic flowchart of a self-assembled small molecule preparation method according to an embodiment of the present invention.

[0041] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention.

[0042] Figure 3 The current density-voltage curves for the forward and reverse scans of the perovskite solar cell prepared in Example 1 of this invention are shown.

[0043] Figure 4 This is a comparison of the current density-voltage curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1 of the present invention.

[0044] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings.

[0045] Icon labels:

[0046] 1. Transparent conductive oxide layer; 2. Perovskite active layer; 21. Self-assembled small molecule film; 22. Perovskite layer; 3. Electron transport layer; 4. Back electrode layer. Detailed Implementation

[0047] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0048] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0049] In this invention, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of that feature. Furthermore, the technical solutions of the various embodiments can be combined with each other, but only on the basis of being achievable by those skilled in the art. If the combination of technical solutions is contradictory or impossible to implement, such a combination of technical solutions should be considered non-existent and not within the scope of protection claimed by this invention.

[0050] This invention provides a method for preparing a perovskite active layer, comprising the following steps: coating a perovskite precursor solution onto the surface of a substrate to form the perovskite active layer; the perovskite precursor solution contains self-assembled small molecules, wherein the self-assembled small molecules include the following structural formulas:

[0051]

[0052] In preparing the perovskite active layer of a perovskite solar cell, this invention adds a self-assembled small molecule, 6,13-bis(triisopropylsilylethynyl)pentabenzene (TIPSp), to the perovskite precursor solution, thereby preparing a perovskite solar cell without pre-deposition of a hole layer. The steric hindrance caused by the thorny triisopropylsilyl group and the large conjugated plane provided by the five benzene rings in the self-assembled small molecule TIPSp of this invention allows the molecule to be orderly squeezed out from the precursor solution to the grain boundaries and the bottom surface of the film. At the same time, the benzene rings are linked to the triisopropylsilyl group through the alkynyl group, resulting in a balanced charge distribution of the molecule. This induces the molecule to have tight stacking and favorable arrangement orientation, forming an ordered, ultrathin hole transport layer at the buried interface of the perovskite active layer. This passivates the interface of the perovskite active layer and improves the interfacial contact of the perovskite active layer. This not only reduces the energy loss during hole transport and provides superior charge transport and charge extraction capabilities, enabling the perovskite solar cell to obtain better device performance, but also eliminates the need to prepare an additional hole transport layer, thus optimizing the fabrication process of the perovskite solar cell.

[0053] The method for preparing the self-assembled small molecules of the present invention includes the following steps:

[0054] S10. Dissolve n-butyllithium and triisopropylsilylacetylene in tetrahydrofuran to obtain a mixture, and dissolve compound A in tetrahydrofuran to obtain a solution of compound A;

[0055] S20, the mixture and the solution of compound A are mixed and heated to obtain the reactant. The reactant is then extracted and the solvent is removed to obtain a crude solid.

[0056] S30. Dissolve the crude solid in an organic solvent, add acetic acid and tin chloride dihydrate solution, stir the reaction, and filter to obtain the solid product;

[0057] S40. The solid product is dissolved in acetone and then washed, dried and purified to obtain self-assembled small molecules.

[0058] Compound A is pentabenzene-6,13-quinone, with the following structural formula:

[0059]

[0060] The compounds of the present invention can be purchased commercially or prepared by means of methods in the art.

[0061] This invention provides a method for preparing compound A according to an embodiment, comprising the following steps: dissolving 4.02 g (30.0 mmol) of o-phenylenedialdehyde and 1.68 g (15.0 mmol) of cyclohexanedione in 450 mL of ethanol, adding 15 mL of 15% KOH aqueous solution, causing the solution to turn brown and form a yellow / orange precipitate. To complete the reaction, the mixture is stirred at 60°C for 4 hours, then cooled, the solid is filtered and thoroughly washed with acetone, yielding compound A, which is yellow in color.

[0062] The following explains the steps for preparing self-assembled small molecules using compound A.

[0063] The following is an explanation of step S10: dissolve n-butyllithium and triisopropylsilylacetylene in tetrahydrofuran to obtain a mixture, and dissolve compound A in tetrahydrofuran to obtain a solution of compound A.

[0064] In some embodiments, the molar ratio of n-butyllithium droplets, triisopropylsilylacetylene, and compound A is (30.5–50.5):(30.2–50.2):(6.2–26.2).

[0065] In some embodiments, the molar ratio of n-butyllithium droplets, triisopropylsilylacetylene, and compound A is 40.5:40.2:16.2.

[0066] In some embodiments, step S10 is performed under a nitrogen atmosphere.

[0067] In some embodiments, after dispersing n-butyllithium in a hexane solution, it is then mixed with triisopropylsilylacetylene and tetrahydrofuran to obtain a mixture.

[0068] In some embodiments, tetrahydrofuran includes dried tetrahydrofuran, the temperature of which is 0°C.

[0069] In some embodiments, n-butyllithium is dispersed in a hexane solution to obtain a n-butyllithium solution, triisopropylsilylacetylene is dispersed in tetrahydrofuran to obtain a triisopropylsilylacetylene solution, and then the n-butyllithium solution is added dropwise to the triisopropylsilylacetylene solution to obtain a mixture.

[0070] The following is an explanation of step S20.

[0071] In some embodiments, the mixture is stored at 0°C for 40 to 60 minutes before being mixed with the compound A solution.

[0072] In some embodiments, the temperature of compound A and the mixture before mixing is 0°C.

[0073] In some embodiments, the temperature of the heating reaction is 25°C to 30°C.

[0074] In some embodiments, the heating reaction time is 12h to 15h.

[0075] In some embodiments, the mixture and the solution of compound A are mixed, heated and reacted, and then quenched to obtain the reactants. The quenching reaction can be carried out with hydrochloric acid (HCl).

[0076] In some embodiments, the extraction includes an extractant, which may include CHCl3.

[0077] In some embodiments, the solvent is removed by rotary evaporation and / or filtration to obtain the crude solid.

[0078] In some embodiments, step S20 is as follows: the mixture from step S10 is mixed with the compound A solution, heated to room temperature, and stirred for 12 hours. The reaction is quenched with 15 ml of 10% HCl, then extracted with CHCl3, and the solvent is removed by rotary evaporation. The crude solid obtained is collected by filtration.

[0079] The following is an explanation of step S30.

[0080] In some embodiments, the mass concentration of acetic acid is 50%.

[0081] In some embodiments, each 50 ml of acetic acid with a mass concentration of 50% contains 9.2 g to 12 g of tin chloride dihydrate.

[0082] In some embodiments, the temperature of the stirring reaction is 25°C to 35°C.

[0083] In some embodiments, the stirring reaction time is 20h to 24h.

[0084] In some embodiments, the crude solid is dissolved in an organic solvent, including acetone.

[0085] In this step, the obtained solid product is a blue solid.

[0086] In some embodiments, step S30 is as follows: the crude solid is dissolved in acetone to obtain a crude solid acetone mixture, and a tin chloride dihydrate solution is added dropwise to acetic acid with a mass concentration of 50% to obtain a mixed solution. The crude solid acetone mixture and the mixed solution are mixed and stirred at 25°C to 35°C for 24 hours. The product is then filtered to obtain a blue solid product.

[0087] The following is an explanation of step S40.

[0088] In some embodiments, washing includes a detergent, which includes saturated sodium bicarbonate.

[0089] In some embodiments, drying includes a desiccant, which may include anhydrous magnesium sulfate.

[0090] In some embodiments, purification is performed using high performance liquid chromatography.

[0091] In some embodiments, purification includes rinsing agents, including n-hexane and dichloromethane.

[0092] In some embodiments, the organic solvent in which the solid product is dissolved includes n-hexane, ethyl acetate, and dichloroethane, wherein n-hexane is preferred, and using n-hexane as the organic solvent is beneficial for increasing the yield.

[0093] In some embodiments, the organic solvent is n-hexane, and the volume ratio of n-hexane to dichloromethane is 9:1.

[0094] In some embodiments, the solid product is dissolved in n-hexane, washed with a saturated sodium bicarbonate solution, dried with anhydrous magnesium sulfate, and purified by rinsing to obtain a dark blue solid, which is the self-assembled small molecule of the present invention.

[0095] In some embodiments, refer to Figure 1 The synthetic route of the self-assembled small molecule is as follows: o-phenylenedialdehyde and cyclohexanedione react in an aqueous solution of KOH to obtain compound A. Compound A and triisopropylsilylacetylene are then processed through steps S10 to S40 to obtain the self-assembled small molecule.

[0096] In some embodiments, the amount of self-assembled small molecules added to the perovskite precursor solution is (0.3–10) mg / ml, for example, it can be 0.3 mg / ml, 0.4 mg / ml, 0.5 mg / ml, 0.8 mg / ml, 1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, 3.5 mg / ml, 4 mg / ml, 4.5 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml, etc. It is understood that the amount added (0.3–10) mg / ml refers to 0.3 g to 10 g of self-assembled small molecules dissolved in 1 ml of solvent, the solvent including commonly used organic solvents in the art for dissolving perovskite materials, such as at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0097] In some embodiments, after adding the self-assembled small molecules, stirring and dispersing them at 50°C to 60°C can make the self-assembled small molecules uniformly dispersed in the perovskite precursor solution.

[0098] In some embodiments, the above-mentioned self-assembled small molecules are used as additives in combination with perovskite materials commonly used in the art to prepare a perovskite active layer.

[0099] In some embodiments, a perovskite precursor solution containing self-assembled small molecules can be prepared by mixing perovskite materials well known in the art together. Alternatively, a perovskite precursor solution can be prepared first using perovskite materials well known in the art, and then self-assembled small molecules can be added to the perovskite precursor solution.

[0100] In some embodiments, perovskite materials well known in the art comprise the chemical formula ABX3, wherein A comprises an organic cation or an inorganic cation, such as MA. + FA + Cs + At least one of them, the B site includes a metal cation, such as Pb. 2+ Sn 2+ At least one of them, the X-position includes a halide anion, such as Br - I - Cl - At least one of them.

[0101] In some embodiments, the perovskite materials and self-assembled small molecules described above are dissolved using organic solvents.

[0102] In some embodiments, the organic solvent includes at least one of anhydrous N,N-dimethylformamide (DMF) and anhydrous dimethyl sulfoxide (DMSO).

[0103] In this invention, the substrate includes a transparent conductive oxide layer, and a perovskite active layer is prepared on the surface of the transparent conductive oxide layer. Because self-assembled small molecules are added to the perovskite precursor solution, an ordered and ultrathin hole transport layer can be formed at the buried interface. Therefore, this invention does not require the additional preparation of a hole transport layer.

[0104] In this invention, the perovskite active layer is prepared using a perovskite precursor solution containing self-assembled small molecules, and methods commonly used in the art can be referenced.

[0105] For example, the perovskite active layer was prepared by spin coating, with the spin coating program being 800 rpm to 1200 rpm for 8 to 12 s and 4500 rpm to 5500 rpm for 30 to 35 s respectively. Then, 100 μL of chlorobenzene was added dropwise between 20 and 25 s after the second program started, and the sample was immediately placed on a hot plate at 130°C to 160°C for annealing for 8 to 12 min to form the perovskite active layer.

[0106] The present invention also provides a perovskite battery, which includes a perovskite active layer comprising a perovskite material containing self-assembled small molecules as described above, and having at least all the beneficial effects of the self-assembled small molecules.

[0107] In some embodiments, the perovskite solar cell further includes a transparent conductive oxide layer (TCO layer). The perovskite active layer is disposed on the surface of the TCO layer. The trimethoxysilyl groups in the self-assembled small molecules in the perovskite active layer can form a high-strength bond with the TCO layer through tridentate anchoring, forming an ordered, ultrathin hole transport layer at the buried interface of the perovskite active layer. This passivates the interface of the perovskite active layer and improves the interfacial contact between the perovskite active layer and the TCO layer. This not only reduces energy loss during hole transport and provides superior charge transport and charge extraction capabilities, enabling the perovskite solar cell to achieve better device performance, but also eliminates the need to fabricate an additional hole transport layer, thus optimizing the fabrication process of the perovskite solar cell.

[0108] In some embodiments, the material used to prepare the transparent conductive oxide layer includes at least one of indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), fluorine-doped tin oxide (FTO), and antimony-doped tin oxide (ATO).

[0109] In some embodiments, reference Figure 2The perovskite solar cell of the present invention comprises, from bottom to top, a transparent conductive oxide layer 1, a perovskite active layer 2, an electron transport layer 3, and a back electrode layer 4. The perovskite active layer 2 includes a perovskite layer 22 and a self-assembled small molecule film 21. The perovskite active layer 22 not only performs the functions of light absorption and charge carrier generation, but also forms a hole transport layer effect at the buried interface of the perovskite active layer 2 by adding self-assembled small molecules, which can promote charge extraction and transport. In addition, it can passivate the interface of the perovskite active layer 2, improve the interfacial contact between the perovskite active layer 2 and the transparent oxide layer 1, reduce energy loss during hole transport, and improve charge transport.

[0110] It should be noted that other functional layers may also be provided between the perovskite active layer 2 and the electron transport layer, and between the electron transport layer and the back electrode in the perovskite battery of the present invention. For example, a hole blocking layer is provided between the electron transport layer and the back electrode.

[0111] This invention also provides a perovskite material for use in perovskite batteries. The perovskite material comprises self-assembled small molecules, which include the following structural formulas:

[0112]

[0113] The aforementioned self-assembled small molecule perovskite material is used to prepare the perovskite active layer of perovskite solar cells. It can be used in combination with conventional perovskite materials in the field. The perovskite active layer prepared in this way can form a thin film at the buried interface that can play the role of a hole transport layer, without the need to prepare an additional hole transport layer.

[0114] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0115] Example 1

[0116] 1. Synthesis of self-assembled small molecules

[0117] Preparation of compound A: 4.02 g (30.0 mmol) of o-phenylenedialdehyde and 1.68 g (15.0 mmol) of cyclohexanedione were dissolved in 450 mL of ethanol. 15 mL of 15% KOH aqueous solution was added. The solution turned brown and a yellow / orange precipitate was formed. To complete the reaction, the mixture was stirred at 60 °C for another 4 hours. After cooling, the solid was filtered and thoroughly washed with acetone. The product was a yellow solid (3.95 g, 12.8 mmol; 85%).

[0118] Preparation of self-assembled small molecules:

[0119] S10. Under a nitrogen atmosphere, 16.2 mL of a hexane solution of n-butyllithium (concentration 2.5 M, containing 40.5 mmol of n-butyllithium) was added dropwise to 50 mL of dry tetrahydrofuran (0 °C) containing 9.1 mL of triisopropylsilylacetylene (40.2 mmol) to obtain a mixture; 50 mL of dry tetrahydrofuran was mixed with compound A pentabenzene-6,13-quinone (5 g, 16.2 mmol) to obtain a solution of compound A, which was stored at 0 °C.

[0120] S20. The mixture was kept at 0°C for another 40 minutes, then transferred to a solution of compound A and heated to react at 25°C–35°C for 12 hours. The entire heating reaction was carried out with stirring. After the reaction, the reaction was quenched with 15 ml of 10% HCl, then extracted with CHCl3, and the solvent was removed by rotary evaporation. The crude solid was collected by filtration.

[0121] S30. Dissolve the crude solid in 50 ml of acetone to obtain a crude solid-acetone mixture. Add 9.2 g, 40.5 mmol of stannous chloride dihydrate solution dropwise to 50 ml of acetic acid with a mass concentration of 50% to obtain a mixed solution. Stir the mixed solution at 25℃~35℃ for 24 h. After the reaction is completed, filter to obtain a blue solid product.

[0122] S40. The solid product is dissolved in n-hexane and washed with saturated sodium bicarbonate solution, then dried with anhydrous magnesium sulfate. The product is then purified by high performance liquid chromatography using a 9:1 (v / v) hexane / dichloromethane mixture as the eluent to obtain a dark blue solid (9.5 g, 92%). This dark blue solid is the self-assembled small molecule, referred to as TIPSp.

[0123] 2. Fabrication of perovskite solar cells

[0124] Cleaning ITO conductive glass

[0125] Remove the protective film from the surface of the ITO conductive glass, ultrasonically clean it with deionized water containing detergent, and then ultrasonically treat it in deionized water, acetone, and isopropanol for 20 minutes in sequence.

[0126] Preparation of perovskite active layer

[0127] A mixture of 19.8 mg CsI, 16.2 mg MABr, 20.3 mg MACl, 224.4 mg FAI, and 742.2 mg PbI2 powders was prepared, and 6 mg TIPSp material was added to it. Finally, the mixture was dissolved in 1 mL of anhydrous DMF / DMSO mixed solvent (4 / 1, v / v) and stirred at 60 °C for 2 h to ensure complete dissolution, thus obtaining a perovskite precursor solution.

[0128] 50 μL of perovskite precursor solution was spin-coated onto a conductive glass substrate using spin-coating programs of 1000 rpm for 10 s and 5000 rpm for 30 s. Between 20 and 25 s after the second spin-coating program started, 100 μL of chlorobenzene was added dropwise, and the sample was then annealed at 150 °C for 10 minutes to form the perovskite active layer.

[0129] 3. Fabrication of other functional layers and metal electrode layers

[0130] The substrate, after the above treatment, is placed in a metal vacuum evaporation deposition chamber inside a glove box, and then C with a thickness of 35 nm is deposited sequentially. 60 A BCP film with a thickness of 7 nm, prepared from 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, and an Ag electrode with a thickness of 100 nm were used to ultimately obtain a complete area of ​​0.06 cm². 2 Perovskite solar cell devices.

[0131] Comparative Example 1

[0132] Comparative Example 1 prepared a perovskite solar cell device according to the method of Example 1, except that no self-assembled small molecules were added when preparing the perovskite active layer.

[0133] Performance testing

[0134] Under standard sunlight (AM1.5G) irradiation, the perovskite solar cell was tested for device performance, and the current density-voltage curve of the perovskite solar cell was obtained as follows: Figure 3 and Figure 4 As shown, the forward and reverse scans of the perovskite solar cell device in Example 1 are represented by FS and RS.

[0135] Table 1

[0136]

[0137] Combination Figure 3 , Figure 4As shown in Table 1, in Example 1, a self-assembled small molecule, TIPSp, was added to the perovskite precursor solution during the preparation of the perovskite active layer. The steric hindrance caused by the thorny triisopropylsilyl groups of TIPSp and the large conjugated plane provided by the five benzene rings allowed the molecule to be orderly squeezed out from the precursor solution to the grain boundaries and the bottom surface of the film. At the same time, the benzene rings were connected to the triisopropylsilyl groups through the alkynyl groups, resulting in a balanced charge distribution of the molecule. This induced the molecule to have tight stacking and favorable arrangement orientation, forming an ordered, ultrathin hole transport layer at the buried interface of the perovskite active layer. This not only passivated the interface of the perovskite active layer, improved the interfacial contact of the perovskite active layer, reduced energy loss during hole transport, and provided superior charge transport and charge extraction capabilities, enabling the perovskite battery to obtain better device performance, but also achieved good performance without the need to prepare an additional hole transport layer. The performance was better than that of the perovskite battery prepared without the addition of the self-assembled small molecule in Comparative Example 1.

[0138] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.

Claims

1. A method for preparing a perovskite active layer, characterized in that: The following steps are involved: Applying a perovskite precursor solution to the surface of a substrate to form the perovskite active layer; The perovskite precursor solution contains self-assembling small molecules, and the self-assembling small molecules include the following structural formula:

2. The method for preparing the perovskite active layer according to claim 1, characterized in that: The preparation method of the self-assembling small molecule comprises the following steps: Dissolving n-butyl lithium and triisopropylsilyl acetylene in tetrahydrofuran to obtain a mixture, and dissolving compound A in tetrahydrofuran to obtain a compound A solution; The mixture is mixed with the solution of compound A, and subjected to heating reaction to obtain a reactant, and the reactant is extracted and the solvent is removed to obtain a crude solid; The crude solid is dissolved in an organic solvent, and acetic acid and tin chloride dihydrate solution are added, stirred for reaction, and filtered to obtain a solid product; Dissolving the solid product in an organic solvent, and washing, drying and purifying to obtain the self-assembling small molecule; The compound A is pentadien-6,13-quinone and has the following structural formula:

3. The method for preparing the perovskite active layer according to claim 2, characterized in that: The molar ratio of n-butyl lithium, triisopropylsilyl acetylene and compound A is (30.5-50.5): (30.2-50.2): (6.2-26.2).

4. The method for preparing the perovskite active layer according to claim 2, characterized in that: The mixture is stored at 0° C. for 40 to 60 minutes and then mixed with the compound A solution; and / or, the temperature of the compound A and the mixture before mixing is 0° C.; And / or, the temperature of the heating reaction is 25°C to 30°C; And / or, the heating reaction time is 12h to 15h; And / or, the mixture is mixed with the solution of compound A, subjected to heating reaction and quenching reaction to obtain a reactant, and the quenching reaction is completed with hydrochloric acid; and / or, the extraction comprises an extractant, the extractant comprises CHCl3; And / or, removing the solvent by rotary evaporation and / or filtering to obtain the crude solid.

5. The method for preparing the perovskite active layer according to claim 2, characterized in that: The mass concentration of the acetic acid is 50%; and / or, 9.2 g to 12 g of tin chloride dihydrate is contained in every 50 ml of acetic acid having a mass concentration of 50%; And / or, the stirring reaction temperature is 25°C to 30°C; And / or, the stirring reaction time is 20h to 24h; and / or, the washing comprises a detergent, the detergent comprising saturated sodium bicarbonate; and / or, the drying comprises a desiccant, and the desiccant comprises anhydrous magnesium sulfate; And / or, the purification comprises an eluent, and the eluent comprises n-hexane and dichloromethane.

6. The method for preparing a perovskite active layer according to any one of claims 1 to 5, characterized in that: The addition amount of the self-assembling small molecules in the perovskite precursor solution is (0.3-10) mg / ml.

7. A perovskite battery, characterized in that: The perovskite battery comprises a perovskite active layer prepared by the method for preparing a perovskite active layer according to claims 1 to 6.

8. The perovskite cell according to claim 7, characterized in that: The perovskite cell further includes a transparent conductive oxide layer, and the perovskite active layer is disposed on the surface of the transparent conductive oxide layer.

9. The perovskite battery according to claim 7, characterized in that: The perovskite cell includes, from bottom to top, a transparent conductive oxide layer, a perovskite active layer, an electron transport layer and a back electrode layer.

10. A perovskite material, applied to a perovskite battery, characterized in that: The perovskite material includes a self-assembled small molecule, and the self-assembled small molecule includes the following structural formula: